Causality Between Electricity Supply and Economic Growth in India: An Empirical Investigation - Gupta, Geetu (My University, 2009)
Electricity plays a crucial role in the economy of a country ,especially when the economy of a country is in its developing phase like India .In this study , an attempt has been made to investigate the causality between electricity supply and economic growth in India taking data from 1960-61 to 2006-07 . In order to find out the causal relationship, Granger causality model has been adopted to find whether there is bi-directional or unidirectional causality running from electricity consumption to economic growth or vise versa. The direction of causation between electricity consumption and economic growth has significant implications. If, for example, there is a unidirectional causality running from economic growth to electricity consumption, it may imply that energy policies may be implemented with little adverse or no effects on economic growth. On the other hand, if unidirectional causality runs from electricity consumption to income, reducing electricity consumption could lead to fall income or vice versa and if there is ‘no causality’ in either direction, the co-called ‘neutrality hypothesis’ would imply that energy policies which do not affect economic growth. However , our results suggest that there exists a unidirectional relationship between electricity supply and economic growth in which electricity act as a catalyst for the further expansion of the economy . In this study , we have incorporated the idea of the existence of a hypothetical environmental Kuznet1 curve for electricity intensity . Our results reveal that there exists Electricity Intensity Kuznet curve in India during 1960-61 to 2006-07 period. The shape of this curve shows an inverted U-shape like Environmental Kuznet Curve ( EKC). In addition, we have also tried to find out the relationship between electricity supply and economic growth in the major states of India by adopting panel regression model. For this analysis ,the data for post- reform period from 1990 to 2004 have been used to find the relationship between electricity & growth. While adopting panel regression model across different states of India , it is established that inverse relationship between electricity supply and growth in the backward states, which in turn reduce the intensity, whereas the results are reverse in case of foreword states except Delhi for which the reasons are discussed in this study . The entire study has been classified in four chapters. Chapter- 1 illustrates the significance of electricity in human life. It also sheds light on changes in the structure of power sector in India .In chapter-2 , the existing literature between electricity supply and economic growth has been thoroughly reviewed.Chapter-3 delineates the set of objectives of the study .In addition , it also discusses different methods which are adopted to accomplish our objective. Last but not the least, the estimated ,results and findings of the study have been discussed in detail in chapter-4 .
Keywords: Energy Economics; Energy Growth Causality